Executive's guide to IT governance : improving systems processes with service management, COBIT, and ITIL - Moeller, Robert R. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
Create strong IT governance processes In the current business climate where a tremendous amount of importance is being given to governance, risk, and compliance (GRC), the concept of IT governance is becoming an increasingly strong component. Executive's Guide to IT Governance explains IT governance, why it is important to general, financial, and IT managers, along with tips for creating a strong governance, risk, and compliance IT systems process. Written by Robert Moeller, an authority in auditing and IT governancePractical, no-nonsense framework for identifyi.
pt. 1. IT governance concepts -- pt. 2. Frameworks to support effective IT governance -- pt. 3. Tools and technologies to manage the IT governance infrastructure -- pt. 4. Building and monitoring effective IT governance systems -- pt. 5. Monitoring and measuring enterprise management and board governance -- pt. 6. IT governance and enterprise objectives.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Information technology -- Management; Information technology -- Auditing; Electronic data processing departments -- Auditing; Information technology -- Management; Information technology -- Auditing; Electronic data processing departments -- Auditing; COMPUTERS -- Computer Literacy; COMPUTERS -- Computer Science; COMPUTERS -- Data Processing; COMPUTERS -- Hardware -- General; COMPUTERS -- Information Technology; COMPUTERS -- Machine Theory; COMPUTERS -- Reference; Electronic data processing departments -- Auditing; Information technology -- Auditing; Information technology -- Management; Information technology / Management; Information technology / Auditing; Electronic data processing departments / Auditing; Electronic books